2020
DOI: 10.1371/journal.pone.0240782
|View full text |Cite
|
Sign up to set email alerts
|

Post lockdown COVID-19 seroprevalence and circulation at the time of delivery, France

Abstract: Background To fight the COVID-19 pandemic, lockdown has been decreed in many countries worldwide. The impact of pregnancy as a severity risk factor is still debated, but strict lockdown measures have been recommended for pregnant women. Objectives To evaluate the impact of the COVID-19 pandemic and lockdown on the seroprevalence and circulation of SARS-CoV-2 in a maternity ward in an area that has been significantly affected by the virus. Study design … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 17 publications
1
21
0
2
Order By: Relevance
“…The third study estimated a seroprevalence of 8% among pregnant women admitted to the delivery room in France in May 2020 (42). Mattern et al found that the seroprevalence among pregnant women was similar to that of the general public (42).…”
Section: Pregnancymentioning
confidence: 97%
See 1 more Smart Citation
“…The third study estimated a seroprevalence of 8% among pregnant women admitted to the delivery room in France in May 2020 (42). Mattern et al found that the seroprevalence among pregnant women was similar to that of the general public (42).…”
Section: Pregnancymentioning
confidence: 97%
“…Two of these studies are conducted in Italy between April -June 2020 reported a prevalence of SARS-CoV-2 antibodies of 10.1% and 14.3% in pregnant women in their first trimester screening or at delivery (74,88). The third study estimated a seroprevalence of 8% among pregnant women admitted to the delivery room in France in May 2020 (42). Mattern et al found that the seroprevalence among pregnant women was similar to that of the general public (42).…”
Section: Pregnancymentioning
confidence: 99%
“…To control the pandemic, diagnostic tests such as reverse transcription polymerase chain reaction (RT-PCR) methods were developed [ 1 ]. The results of these RT-PCR tests were used for taking political decisions such as imposing lockdown in several countries [ 2 , 3 ]. However, since RT-PCR tests are feasible only within three weeks since symptom onset, it is inconvenient for epidemiological investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Artigos explicitaram desenvolvimento de conselhos internacionais para parteiras, outros profissionais de saúde e gerentes de serviços de saúde sobre o cuidado de mulheres e seus bebês durante o parto; adoção de um sistema paternalista de abordagem ao parto somado ao medo das gestantes; esclarecimento às suposições acerca do risco da COVID-19 no terceiro trimestre da gravidez; e estabeleceram um comparativo entre o número de gestantes e não gestantes que testaram positivo identificando de forma precoce de qualquer impacto psicológico que ocorra na gestação [7,[13][14][15][16].…”
Section: Tabela II -Resultados Encontrados Nos Estudos De Acordo Com Os Níveis De Evidências Objetivos E Conclusões Recife Pe Brasil 2021unclassified